A Generalised Mathematical Model of Electricity Consumption for Electric Drives in Smart Cities Applications - Shevchenko, A.; Kolupaieva, I.; Romashov, Y. (My University, 2025)
The generalised mathematical model of electricity consumption is developed by using electromechanical analogies and Lagrange's equations of 2-nd kind in the view of the system of two first order and one two order ordinary differential equations with the related initial conditions. It allows representing the dependency between supplied voltage and the electricity consumption of the electric drive. This mathematical model is for following researches directed to formulate and to solve the problem of the optimal control theory, so that it allows developing the energy efficient automated controls for electric drives required in smart cities applications
Keywords: electricity consumption; electric drive; smart sites